PEMANFAATAN BALAI LADUMA SEBAGAI ALTERNATIF PENGEMBANGAN AKTIVITAS DAYA TARIK RAMAH LINGKUNGAN DI DESA WISATA PINGE - Feliciano Luis Dos Santos Martins,; Putu Diva Krisna Maharani,; Rediyanti Takarina Basuki,; I Wayan Kiki Sanjaya,; Komang Shanty Muni Parwati, (JURNAL PENGABDIAN MANDIRI, 2023)
Balai Laduma is a tourist destination located in Pinge Tourism Village, Tabanan Regency, Bali. This community service aims to utilize Balai Laduma as an alternative to developing environmentally friendly attraction activities in the Pinge Tourism Village. Implementation methods used include surveys and observations. The results of this dedication show that using Balai Laduma as an environmentally friendly tourist destination can improve the community's economy and positively impact the environment. The conclusion of this dedication is that Balai Laduma can be used as a sustainable eco-friendly tourist destination in the Pinge Tourism Village.